Análisis del índice de selección del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Pastocalle del cantón Latacunga. - Villarreal Ortiz, Zayda Mercedes (2024)
In Ecuador, Cotopaxi province stands out in the dairy industry as one of the most significant economic sectors. However, small and medium-sized producers lack detailed cost records, affecting the accuracy of individual benefits. This situation forces residents to seek additional sources of income. Thus, a study was conducted in the Pastocalle parish from September to November 2023. The research collaborated with 10 dairy producers, evaluating 96 cattle, including calves, bulls, lactating cows, and dry cows managed through practices such as tethering and grazing. Economic results reveal a selling price of 0.43 cents per liter, with a production cost of 0.28 cents, yielding a profit of 0.15 cents. Daily weight gain demonstrated a phenotypic average of 367 g/day, while the genetic value of the 10 selected animals is 86.45 grams daily. Regarding milk production, an average genetic value of 3069.75 liters per lactation was obtained. Additionally, in terms of density, an average of 1.026 g/ml was recorded. Although milk production stands out, areas for improvement in weight gain and density are noted. Implementing a genetic improvement program is suggested, with ongoing monitoring to optimize future outcomes.